An Analysis of Derivational Morphology in Angelina Jolie’s UN Speech on Equality for Women - Meidi Kulsum, Eva; Halimatus Sadiah, Alviani (Science, Tecnology, Religious, Economic, and Social Humanitis (STREAS), 2025)
This study aims to discuss derivational affixes in Angelina Jolie’s speech at the UN on women’s equality. This study uses a descriptive qualitative method in analysing the derivation words in Angelina Jolie's speech. The results found 78 derivation words, which consist of 16 prefixes (e.g. -in-, -re-, -epi-) and 62 suffixes (e.g -ity-, -ment-. -tion-). Prefixes are used to create a new meaning of the base word without changing the word class such as the prefix -in- on the word inequal and prefix -un- in the word unwilling the other hand, the addition of suffixes to the base word often changes the word class. A significant change is the change in verbs or adjectives into nouns as much as 73.3% when suffixes are added to verb or adjective base words such as the example of the word govern becomes government. The other change from noun to adjective is 20% as in the word politics becomes political last change of adjective to adverb as much as 6.7% as in the word peaceful becomes peacefully. The findings show a pattern of word formation through the derivational process that emphasizes its role in modifying meaning and grammatical function in the context of formal speech.